Presumption of the Mandator’s Property in Private Law Doctrine and Judicial Practice - Putkaradze, Revaz (Journal of Law, 2025)
In both substantive civil law relations and civil procedural law, the category of presumptions has crucial importance. Legal doctrine and judicial practice recognize and apply two types of presumptions: legal (statutory) presumptions and factual, or judicial presumptions. The significant role of presumptions is due to, on the one hand, by the need for accurate legal qualification of the legal relationship existing between the parties and, on the other hand, by the necessity of the correct allocation of the burden of proof. The subject matter of this research is narrow in scope. It does not aim to provide a comprehensive analysis of the category of presumptions in law, which would in any event be impossible within the framework of a single article. Instead, the study focuses on one specific legal presumption, the presumption of the mandator’s property in private law. The provision containing this presumption, enshrined in Article 716 of the Civil Code of Georgia, is a multifaceted norm, which leads to difficulties in qualifying the legal relationships regulated by it. In Georgian legal scholarship, this problem has not been examined as an independent subject of research. However, practice clearly demonstrates the practical significance of legal relationships that arise in one’s own name but at the expense of the mandator. The correct application of the norm is impossible without adequate scholarly research. Accordingly, the aim of this study is to determine the precise legal meaning of the provision on the presumption of the mandator’s property, its scope of application, the addressee of the norm, the content and nature of the legal relationship arising from it, and whose interests the given norm serves. As a result of examining this problem, the functional purpose of the institution provided for by the norm will be identified, along with the cases in which the application of the norm is permissible and the types of relationships regulated by it. This, in turn, will enable courts to apply the norm correctly, contribute to the formation of consistent judicial practice, and foster the development of private law doctrine.